2004
DOI: 10.1016/j.crvi.2004.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Using wood creep data to discuss the contribution of cell-wall reinforcing material

Abstract: Longitudinal four-point creep bending tests were performed on small clear-wood spruce specimens having various microfibrillar angles. Cell-wall compliance was deduced from macroscopic data by accounting for porosity. Time-dependent compliance was converted into complex compliance and rigidity using the value and the slope of the compliance versus logarithm of time. Complex rigidity plots of all specimens, for the time range 10 3 -10 6 s, could be superimposed by a horizontal shift depending on the microfibrill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…All three of these forms of deformation of wood seem to be focused in the matrix region between microfibrils or microfibril aggregates, and increase simultaneously in magnitude with microfibril angle (Bengtsson, 2001; Fratzl et al, 2004; Gril et al, 2004), but it does not follow that they share exactly the same mechanism. There is an interesting parallel with the unexplained observation that stress relaxation parameters for the stretching of primary walls often correlate with growth (Nakamura et al, 2002).…”
Section: Biomechanics Of Secondary Cell Wallsmentioning
confidence: 97%
See 1 more Smart Citation
“…All three of these forms of deformation of wood seem to be focused in the matrix region between microfibrils or microfibril aggregates, and increase simultaneously in magnitude with microfibril angle (Bengtsson, 2001; Fratzl et al, 2004; Gril et al, 2004), but it does not follow that they share exactly the same mechanism. There is an interesting parallel with the unexplained observation that stress relaxation parameters for the stretching of primary walls often correlate with growth (Nakamura et al, 2002).…”
Section: Biomechanics Of Secondary Cell Wallsmentioning
confidence: 97%
“…The viscous component increases with the angle between the microfibrils and the stress (Bonfield et al, 1996; Gril et al, 2004) and has been modeled as due to viscous shear in the lignin–hemicellulose matrix between elastic microfibrils (Engelund and Svensson, 2011) or microfibril aggregates. The calculated free energy of activation was consistent with the breaking of four to six hydrogen bonds in each sliding event (Bonfield et al, 1996).…”
Section: Biomechanics Of Secondary Cell Wallsmentioning
confidence: 99%
“…For instance, the modulus of elasticity (MOE) decreases with increasing MFA (Persson 2000). Also, the TDMB of wood is influenced by the MFA (Gril et al 2004;Kojima and Yamamoto 2004).…”
Section: Tracheid Structure and Mechanical Behaviourmentioning
confidence: 99%
“…Often these models assume contributions from elastic, viscoelastic, and viscous components. However, the physical interpretation of the parameters applied in such models is often difficult (Hunt 1997;Gril et al 2004). This is because these mathematical models typically are not related to the physical mechanisms behind the observed mechanical behaviour (Hunt 1997).…”
Section: Introductionmentioning
confidence: 97%
“…In fact, a wood cell wall can be considered as a fiber-reinforced composite (Cave, 1968), therefore the mechanical properties along microfibril direction are superior to other directions. On the other hand, MFA is also found to be an important factor in determining wood viscoelastic properties: in dry wood, a positive relation is generally found between MFA and the damping coefficient (tanδ) obtained by dynamic tests (Norimoto et al, 1986), and in quasi-static creep test, the creep compliance is found to be strongly related to MFA (Gril et al, 2004;Kojima and Yamamoto, 2004). In fact, it is a usual methodology to compare directly the dynamic modulus and damping coefficient in evaluating the acoustic properties of woods.…”
Section: Introductionmentioning
confidence: 99%